2000
DOI: 10.4049/jimmunol.164.1.176
|View full text |Cite
|
Sign up to set email alerts
|

Glycine Inhibits Growth of T Lymphocytes by an IL-2-Independent Mechanism

Abstract: Previously, it was shown that glycine prevented increases in intracellular calcium ([Ca2+]i) in Kupffer cells. Since Kupffer cells and T lymphocytes are derived from the same pluripotent stem cell, it was hypothesized that glycine would prevent increases in [Ca2+]i in lymphocytes and inhibit cell proliferation. Lymphocyte proliferation was measured in one-way MLC with spleen cells from DA and Lewis rats and in enriched T lymphocyte preparations stimulated by immobilized anti-CD3 Ab. Glycine caused a dose-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 40 publications
3
27
0
Order By: Relevance
“…Consistent with this view, Boncristiano et al (17) recently reported that VacA could block ionophore-stimulated inf lux of calcium into T cells. Furthermore, a previous study demonstrated that activation of glycine-gated chloride channels induces membrane depolarization of T cells, resulting in a decreased open probability of plasma membrane calcium channels and in the inhibition of IL-2-dependent proliferation without affecting IL-2 secretion or NFAT activation (37).…”
Section: Discussionmentioning
confidence: 97%
“…Consistent with this view, Boncristiano et al (17) recently reported that VacA could block ionophore-stimulated inf lux of calcium into T cells. Furthermore, a previous study demonstrated that activation of glycine-gated chloride channels induces membrane depolarization of T cells, resulting in a decreased open probability of plasma membrane calcium channels and in the inhibition of IL-2-dependent proliferation without affecting IL-2 secretion or NFAT activation (37).…”
Section: Discussionmentioning
confidence: 97%
“…Our own data are consistent with a requirement for sustained RyR-mediated intracellular Ca þþ mobilization by T cells in response to IL-2 receptor signaling since (1) anti-CD3-activated T cells that had normal CD25 expression failed to proliferate in response to exogenous IL-2 when RyR were blocked by ruthenium red and (2) IL-2-dependent mouse CTLL-2 cells exhibited a reduced capacity to proliferate in response to IL-2 in the presence of RyR antagonists. In this regard, it is noteworthy that glycine, which blunts anti-CD3-induced increases in intracellular Ca þþ concentration in rat T cells, also inhibits the IL-2-dependent proliferation of mouse CTLL-2 cells [Stachlewitz et al, 2000]. One possibility is that RyRmediated increases in intracellular Ca þþ levels are required for the activation of kinases that regulate T cell proliferation in response to IL-2 receptor signaling.…”
Section: Intracellular Camentioning
confidence: 99%
“…It can stimulate glycine-gated chloride channels, leading to increased chloride influx that hyperpolarizes neuronal membranes and inhibits excitatory signal transduction (4,26). Recently, glycine has been shown to be immunosuppressive in several studies (35,40). Glycine ameliorates kidney and liver injury during endotoxin shock (12), an effect that was due to the blocking of intracellular calcium signaling and the production of TNF-␣ in hepatic Kupffer cells via a glycine-gated chloride channel (13,41).…”
mentioning
confidence: 99%